Effect of Proinflammatory Cytokines (IL-6, TNF-α, and IL-1β) on Clinical Manifestations in Indian SLE Patients - Vinod Umare; Vandana Pradhan; Milind Nadkar; Anjali Rajadhyaksha; Manisha Patwardhan; Kanjaksha K. Ghosh; Anita H. Nadkarni (Mediators of Inflammation)
Systemic lupus erythematosus (SLE) is an inflammatory rheumatic disease characterized by production of autoantibodies and organ damage. Elevated levels of cytokines have been reported in SLE patients. In this study we have investigated the effect of proinflammatory cytokines (IL-6, TNF-α, and IL-1β) on clinical manifestations in 145 Indian SLE patients. One hundred and forty-five healthy controls of the same ethnicity served as a control group. Clinical disease activity was scored according to SLEDAI score. Accordingly, 110 patients had active disease and 35 patients had inactive disease. Mean levels of IL-6, TNF-α, and IL-1β were found to be significantly higher in SLE patients than healthy controls (P<0.001). Mean level of IL-6 for patients with active disease (70.45±68.32 pg/mL) was significantly higher (P=0.0430) than those of inactive disease patients (43.85±63.36 pg/mL). Mean level of TNF-α was 44.76±68.32 pg/mL for patients with active disease while it was 25.97±22.03 pg/mL for those with inactive disease and this difference was statistically significant (P=0.0161). Similar results were obtained for IL-1β (P=0.0002). Correlation between IL-6, TNF-α, and IL-1β serum levels and SLEDAI score was observed (r=0.20, r=0.27, and r=0.38, resp.). This study supports the role of these proinflammatory cytokines as inflammatory mediators in active stage of disease.